2011
DOI: 10.1093/infdis/jir426
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Innate and Adaptive Immune Mediators in Human Corneal Tissue Infected With Aspergillus or Fusarium

Abstract: There is a common innate and adaptive immune response to these filamentous fungi, which includes the generation of T-helper 1 and T-helper 17 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 46 publications
6
87
0
2
Order By: Relevance
“…64 Pseudomonas aeruginosa in mice is able to activate the NLRC4 inflammasome via immune cell internalisation of its bacterial flagellin, as well as via components of its type 3 secretion system. 65 Streptococcus pneumoniae …”
Section: Innate Immune Cells In the Mammalian Corneamentioning
confidence: 99%
“…64 Pseudomonas aeruginosa in mice is able to activate the NLRC4 inflammasome via immune cell internalisation of its bacterial flagellin, as well as via components of its type 3 secretion system. 65 Streptococcus pneumoniae …”
Section: Innate Immune Cells In the Mammalian Corneamentioning
confidence: 99%
“…Our recent studies characterizing fungus-infected human corneas in India showed that neutrophils constitute greater than 90% of cellular infiltrates in corneal ulcers in patients infected for less than 7 days and more than 70% total infiltrate at later stages of infection (18). Similarly, neutrophils are the first cells recruited to the corneal stroma in murine models of Aspergillus and Fusarium keratitis (19,20), indicating that neutrophils are the main effector cells required for killing fungal hyphae.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated expression of the cytokines IL-1b, IL-6, IL-8, and TNF-a has been shown in a number of inflammatory cornea pathologies. 30,31 The elevation of these cytokines results in angiogenesis, inflammation, and sterile ulcer formation due to their upregulation of MMP-9. [31][32][33] However, a recent study demonstrated no increase in these cytokines in the tear fluid of rosacea patients and an upregulation of these cytokines in ocular rosacea patients was not observed.…”
Section: Discussionmentioning
confidence: 99%